Listening to Country: Immersive Audio Production and Deep Listening with First Nations Women in Prison - Woodland, Sarah; Barclay, Leah; Saunders, Vicki; Beetson, Bianca (Performance Matters, 2022)
Listening to Country was an arts-led research project where, as an interdisciplinary team of practitioner-researchers, we worked with incarcerated Aboriginal and Torres Strait Islander women to produce a one-hour immersive audio work based on field recordings of natural environments. The project began with a pilot phase in Brisbane Women’s Correctional Centre (BWCC), Australia, to investigate the value of acoustic ecology in promoting wellbeing among women who were experiencing separation from family, culture, and Country (ancestral homelands). The team facilitated a three-week program with the women, using arts-led processes informed by visual art, performance, Indigenous storywork, and dadirri (deep, active listening). The soundscape presented here is a response to the creative process that we led inside the prison and the audio work that the incarcerated women co-created with the research team. The accompanying text describes the background to the original project, the process we undertook in the prison, and our methodology for translating knowledge from the research based on the acoustic and poetic resonances of our experience.